Creatine loading, resistance exercise performance, and muscle mechanics - Stevenson, W.; Dudley, G. A. (The Journal of Strength and Conditioning Research, 2001)
We tested the null hypothesis that creatine monohydrate loading (20 g per day for 7 days, n = 18) would not alter resistance exercise performance, isometric strength, or in vivo contractile properties of the quadriceps femoris muscle compared with loading with placebo (n = 13) in resistance-trained subjects. For the entire study group, the 1 repetition maximum (1RM) and 5-set performance (the number of repetitions) for unilateral, dynamic knee extension increased slightly (2% and 5%, respectively) after dietary supplementation, and these responses did not differ by condition. Maximal voluntary isometric torque and the rate of torque development did not change. During electromyostimulation, torque development and relaxation time were also unaffected. Our data suggest that creatine loading does not augment unilateral strength or multiset resistance exercise performance for knee extensions compared with placebo loading.